Going Out into the World: the “Strategic Approach” of Jewish Members of the Imperial Order of the Daughters of the Empire, 1900-1939 - Klassen, Magdalene (Canadian Jewish Studies / Études juives canadiennes, 2019)
The Imperial Order of the Daughters of the Empire (IODE) was a non-sectarian women’s patriotic association that sought to bolster Canada’s British character. During the interwar period, members dedicated themselves to the “canadianization” of non-British immigrants. Though the Order was overwhelmingly Anglo-Protestant, many established Jewish women joined, embodying a “strategic” approach to humanitarianism. This paper concentrates on the participation of two sisters who joined non-denominational chapters, Irene Wolff and Rosetta Joseph, as well as Montreal’s Jewish “Grace Aguilar” chapter. By joining the Order, these elite Jewish women sought to establish a relation of imperial kinship that could influence dominant Anglo-Canadian perceptions of and policy towards the nation’s Jewish citizens. The efforts of these women suggest the limits and possibilities of a preservationist respectability politics: by the interwar period, the IODE’s vision of British supremacy was increasingly obsolete and demographic changes had irrevocably transformed the character of Canadian Jewish life.